Chemical And Organoleptic Quality Of Suction Pudding With Variations In The Type And Concentration Of Carrot Extract (Daucus carota L.) - L Listiana; Kurnia Hartati, Fadjar; Bambang Sigit (SAGA: Journal of Technology and Information System, 2023)
Carrots are one type of vegetable that is rich in vitamin A. In order to increase carrot consumption, it is necessary to diversify carrot-based preparations, among others, by adding carrots to the pudding suction. This study aims to determine the effect of the interaction of the type and concentration of wotel extract on the chemical and organoleptic quality of lipo pudding as functional food. The research method used is experimental laboratory with Complete Random Design (RAL) research design which is arranged factorially with 2 (two) factors. The first factor is the type of carrot extract, namely boiled carrot extract and fresh carrot extract. The second factor is the difference in carrot extract concentration, which is 7%, 10% and 13% carrot extract. Each treatment factor was repeated 3 (three) times resulting in 18 trials. Observational variables include β-carotene tests, crude fiber tests, reduction sugar tests, and organoleptic tests. Based on the results of the study showed that the interaction between different types and carrot extracts had no real effect on β-carotene levels, crude fiber levels, sugar reduction levels. The best treatment in this study was the F2B treatment, namely suction pudding with the addition of fresh carrot extract with a concentration of 10% with the highest Yield Value (NH) of 0.87. The criteria for the parameters of the study were β-carotene content = 983.0 ppm, crude fiber content = 2.1%, reduced sugar content = 14.37%, color = 5.05 (somewhat like), taste = 5.07 (somewhat like), aroma = 4.67 (somewhat like), and chewiness = 4.71 (somewhat like).